2017
DOI: 10.1007/s10126-017-9746-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of Mycosporine-Like Amino Acids from Gracilaria vermiculophylla (Rhodophyta) Cultured Through One Year in an Integrated Multi-trophic Aquaculture (IMTA) System

Abstract: This study evaluates the production of biomass and mycosporine-like amino acids (MAAs) throughout the year in Gracilaria vermiculophylla (Rhodophyta) collected in Ria de Aveiro (Portugal). The algae were grown in outdoor tanks in seawater with the addition of fishpond effluents under two different water flows (100 and 200 L h) in an integrated multi-trophic aquaculture (IMTA) system (tanks 1200 L; 1.5 m) and different algal densities (3, 5, and 7 kg m). MAA content in IMTA seaweeds was significantly affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…Lalegerie et al [14] found eight different MAAs in the same species, some of them unidentified, but no total MAA concentration was shown. Barceló-Villalobos et al [32] identified four MAAs, the same as in this work, porphyra-334, shinorine, palythine, and asterina-330. However, total MAA concentration of samples collected from the field was at least two times higher than our MAA concentration.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Lalegerie et al [14] found eight different MAAs in the same species, some of them unidentified, but no total MAA concentration was shown. Barceló-Villalobos et al [32] identified four MAAs, the same as in this work, porphyra-334, shinorine, palythine, and asterina-330. However, total MAA concentration of samples collected from the field was at least two times higher than our MAA concentration.…”
Section: Discussionsupporting
confidence: 78%
“…In order to study the influence of distilled water, as a solvent of extraction in MAA analysis, four Rhodophytes were selected based on their medium-high MAA contents and their different MAA profiles [17,31,32]: Agarophyton vermiculophyllum, Crassiphycus corneus, Gracilariopsis longissima, and Pyropia leucosticta. We selected different procedures and two HPLC columns that are commonly used for MAA analysis in order to elucidate which procedure would be the best option for the isolation, identification, and quantification of MAAs for cosmetic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Structure, molar extinction coefficient, retention time, and maximum absorption wavelength of MAAs in marine macroalgae [43,95]. In addition, it is worth mentioning that the difference of the total MAAs or MAA value between cultivated marine macroalgae and field material existed from same collection location.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Structure, molar extinction coefficient, retention time, and maximum absorption wavelength of MAAs in marine macroalgae [43,95]. In order to clearly present the distribution of specific MAA in each marine macroalgae, based on the literature information from the Web of Science, Springer, Google Scholar, and CNKI, Tables 2 and 3 are presenteed.…”
Section: Introductionmentioning
confidence: 99%
“…In such systems, the seaweed utilizes the animals' metabolic waste as fertilizer while absorbing CO 2 and releasing O 2 to the environment. The seaweed of economic potential cultivated in IMTA is doubly interesting, since it reduces environmental impact and provides biomass for the extraction of high-value compounds (Samocha et al 2015;Yu et al 2016;Barceló-Villalobos et al 2017). In addition, IMTA has the potential to contribute to a positive, sustainable image, and improved social acceptability (Barrington et al 2010).…”
Section: Introductionmentioning
confidence: 99%